Scoping Review of Extraction Methods for Detecting β-Lactam Antibiotics in Food Products of Animal Origin - Joanna Pacyńska; Przemysław Niedzielski (Molecules)
The widespread use of β-lactam antibiotics in veterinary medicine and food production has contributed to the rise of antibiotic-resistant bacteria, posing significant health risks to humans. This issue is recognized by various regulatory agencies, which settled maximum residue limits (MRLs) for antibiotics in animal-derived foods. To adhere to these regulations, sensitive and selective methods are required for monitoring antibiotic residues. Due to the critical importance of sample preparation in the analysis, numerous extraction techniques have been developed. This review focuses on various methodologies for extracting β-lactam antibiotics from different food matrices. The paper summarizes the procedures for the extraction of β-lactam antibiotics identified in the literature, indicating their detailed methodology. The summary may be useful for any laboratories preparing new applications for the determination of antibiotics in food. Research studies analyzed in the paper were collected from databases, such as Google Scholar, PubMed, and Scopus. After a close evaluation of about 200 articles (published between 2010 and 2024), 35 of them, which met the criteria, were included in the analysis.